Additions to the Genus Arthrinium (Apiosporaceae) From Bamboos in China - Feng, Yao; Liu, Jian-Kui (Jack); Lin, Chuan-Gen; Chen, Ya-Ya; Xiang, Mei-Mei; Liu, Zuo-Yi (Frontiers in Microbiology, 2021)
Arthrinium has a widespread distribution occurring in various substrates (e.g. air, soil debris, plants, lichens, marine algae and even human tissues). It is characterized by the basauxic conidiogenesis in the asexual morph, with apiospores in the sexual morph. In this study, seventeen isolates of Arthrinium were collected in China. Based on their morphology and phylogenetic characterization, four new species (A. biseriale, A. cyclobalanopsidis, A. gelatinosum and A. septatum) are described and seven known species (A. arundinis, A. garethjonesii, A. guizhouense, A. hydei, A. neosubglobsa, A. phyllostachium and A. psedoparenchymaticum) are identified, of which the sexual morph of three species (A. guizhouense, A. phyllostachium and A. psedoparenchymaticum) and asexual morph of A. garethjonesii are reported for the first time. The detailed descriptions, illustrations and comparisons with related taxa of these new collections are provided. Phylogenetic analyses of combined ITS, LSU, TUB2 and TEF sequence data support their placements in the genus Arthrinium and justify the new species establishments and identifications of known species.